Integrating Battery Energy Storage Systems in Hot Desert Regions - Maher, Kenza; Kubiak, Pierre; Cen, Zhaohui (IEEE ... International Conference on Renewable Energy and Power Engineering (Online), 2023)
The increasing utilization of solar renewable energy sources in the Gulf Cooperation Council (GCC) regions, including countries such as Saudi Arabia, the UAE, and Qatar, highlights the pressing need for Battery Energy Storage Systems (BESS) to ensure grid stability BESS plays a crucial role in storing excess energy generated during peak generation and supplying it during periods of low generation or high demand. However, integrating BESS in hot desert regions presents unique challenges due to the extreme environmental conditions prevalent in these areas. High ambient temperatures, dust and sandstorms, and intense solar radiation intensity pose obstacles that must be addressed to maximize the effectiveness of BESS deployment. This study aims to identify these obstacles and propose effective solutions for the integration of BESS in hot desert regions. The environmental challenges are analyzed in-depth, considering the impact of high ambient temperatures on battery performance, the accumulation of dust and sand on system components, and the effects of intense solar radiation on system efficiency. By addressing the challenges associated with integrating BESS in hot desert regions, this study contributes to the broader goal of driving sustainable energy solutions in Qatar and the GCC region.